Field study of drilling bits performance optimization using a computer model. (2015)
One of the major problems facing drilling operations is the performance of the drilling Bits. The ability of the Bit to crush the rock and the removal of the crushed rock from the wellbore effectively. It is necessary to understand the fundamental difference in Bit design for different rock textures because many variables tend to affect Bit optimization, particularly the type of formations, economics and Bit selection. However, the cost of drilling a well has a considerable effect on the selection and the design of a particular Bit, therefore this paper focuses on the development of a model that will predict future Bit performance and optimization for actual well design and construction. The variables to optimize Bit performance provide means of handling cost estimation hence the model becomes more realistic and dynamic in its application. The input variables and control factors for this model are stretched to minimize cost and maximize performance. The cost per foot and the break even calculations were done using data from the reference well X14 and also the evaluation well X35 from a field-X in the Niger Delta region. A Visual Basic dot Net program model was developed, tested and validated with the real field data to know its accuracy. The model interface shows the detailed application of the Bits in validating the data to provide the equivalent results for the five different Bits. Each set of the Bit record was ran separately on the software and the results for each application developed for comparison. In the software, data application were grouped into two distinct methods namely; rentals method and historical method. Under the rentals method, data were uploaded into the software and ran to generate results while the historical method was basically used for model prediction. The breakeven analysis provided a technique for calculating the performance required for an alternative Bit type to match the cost per foot of the current Bit. Based on the model results, Hughes Tungsten Carbide (HTC) Bit and Security Bit (SEC) used to drill well X14 and X35 were well optimized and should be encouraged in drilling wells within the area.